Marco conceptual para la evaluación de programas de salud - Montero Rojas, Eiliana (2004)
Evaluation, as a discipline, is an relatively new area of the Social Sciences, thus, its explicit incorporation in health programs and systems has appeared somehow late. This article presents elements of a conceptual framework to conceive and use the evaluation in health programs. Evaluation is defined as a tool for decision making, current tendencies and themes in the field are discussed, as well as key concepts such as program theory and needs assessment. Finally, a first approach to two key concepts in evaluation of health programs, quality and equity, is presented.